Pengaruh Yoga dalam Meningkatkan Kualitas Tidur Ibu Hamil Trimester III di Wilayah Kerja Puskesmas Kabun - Fitria, Rahmi; Nismayati; Sepduwiana, Heny; Nurkhasanah, Siti (Jannatul Makwa Health : Jurnal Ilmiah Kesehatan (Scientific Journal of Health), 2025)
Pregnancy is a natural process that women experience during this period of their lives. Pregnancy causes excessive conditioning and fatigue, this is because your body is working actively to adapt physically and emotionally to this pregnancy, one of the discomforts that often arises is disturbed sleep patterns. One way to overcome poor sleep patterns is to do yoga, which is one of the light exercises that pregnant women can take. This research aims to. find out the effect of yoga in improving the sleep quality of pregnant women in the third trimester in the working area of ​​the Kabun Health Center. This research method is quantitative using the Pre-experiment method with a one group pretest-posttest design approach. The sampling technique in this research is a purposive sampling technique where the samples used for research are those that meet certain criteria, namely 25 respondents. for data analysis using the T-Dependent statistical test, the p-value = 0.000, thus, p-value (0.000) < 0.05, which indicates that there is an influence of yoga in improving the sleep quality of pregnant women in the third trimester in the working area of ​​the Kabun Community Health Center, Rokan Hulu Regency.